Antifibrinolytic Use and Blood Transfusions in Pediatric Scoliosis Surgeries Performed at US Children's Hospitals. Issue 8 (October 2015) - McLeod, Lisa M.; French, Benjamin; Flynn, John M.; Dormans, John P.; Keren, Ron
<x xml:space="preserve">Abstract</x> Study Design: Retrospective cohort study using the Pediatric Health Information Systems database. Objective: To determine the association between antifibrinolytic use and red cell transfusions in spinal fusion operations performed at 37 US Children's Hospitals. Summary of Background Data: Evidence from randomized clinical trials and systematic reviews suggests that antifibrinolytic therapy can significantly reduce blood loss in children undergoing scoliosis surgery; however, the effectiveness of these agents as used in surgeries performed at US children's has not been studied. Materials and Methods: We included children aged 0–18 years with diagnoses indicating adolescent idiopathic scoliosis (AIS) or neuromuscular scoliosis (NMS) for whom a spinal fusion procedure was performed between January 1, 2006 and September 30, 2009. Patients with malignancy, trauma, coagulation disorders, or for whom a cell salvage device was employed were excluded. Multilevel logistic regression was used to determine associations between ε-aminocaproic acid (EACA), tranexamic acid (TXA), and aprotinin (APR) use and blood transfusions, controlling for patient and surgery characteristics. Results: Cohorts consisted of 2722 AIS and 1547 NMS procedures. Antifibrinolytic use varied across hospitals (AIS 3.3%, interquartile range, 0%–42%; NMS 12 interquartile range, 0%–46%), and was significantly associated with NMS, posterior fusion, number of vertebrae fused. Overall, 15% of children received EACA, 7% TXA, and 2% APR. The median hospital-specific rate of red cell transfusions was 24% for AIS and 43% for NMS. In AIS operations, EACA use, but not TXA use, was associated with significantly lower odds of transfusion (odds ratio, 0.42; P<0.001 vs. odds ratio, 1.0; P=0.8). In NMS operations, neither EACA nor TXA use was associated with a decrease in odds of red cell transfusions. Conclusions: The effectiveness of antifibrinolytics as used outside of clinical trials is unclear and should continue to be explored. Future prospective research is needed to evaluate which administration protocols will most benefit patients, as well as to determine the comparative effectiveness of these drugs in the context of other blood conservation strategies.